On Theory Construction and Verification. - Sterling, Robert R. (The Accounting Review, 1970)
The article presents an analysis of the nature of empirical theories for the purpose of providing a relief for some current and proposed theories of accounting. The process of theory construction is imperfectly understood. Even though it is not clear how theories are constructed, however, one can note that a new theory usually arises as a result of "anomalies" in the old theory. The purpose of the new theory or the modified theory is to make the unexpected expected, to convert the anomalous occurrence into an expected and explained occurrence. Theories are expressed in a language, and therefore the study of language is pertinent to the study of theories. A theory of empirical science may be divided into two parts, first, a Formal System which is composed of abstract symbols and a set of syntactical rules for manipulating those symbols; and second, an Interpretation of the formal system which connects certain symbols to observations via semantical rules. One of the difficulties encountered in accounting theory construction and verification is that different accounting theories are often theories about different subject matters.